Evaluation of Hospitalization in Emergency Care Units in the West of Paraná due to Primary Care Sensitive Causes (Research, Society and Development, 2022)
Objective: To define and evaluate the causes of hospitalizations due to Primary care-sensitive conditions in Emergency Care Units in Cascavel-PR. Methodology: Qunatitative, observational, cross-sectional and prospective study, developed through data collection and analysis (name, gender, age, neighboorhood, length of stayand primary cause of hospitalization) contained in medical records of users of the Emergency Care Units of Cascavel-PR, who were waiting for a hospital vacancy and hospitalizaed for more than 24 hours. Results and discussion: Between September and November 2021, 451 medical records were analyzed. As for age, there is an increase in the number of patients concomitantly with advancing age. There was no significant finding regarding the gender variable. There was a predominance of hospitalizations for a period close to 24 hours. The most common causes of hospitalization were Covid-19 and psychiatric illness. AMong the 3 sanitary districts of Cascavel, there were proportionately more hospitalizations of patients from district 2. A greater number of hospitalizations was identified in the Brasília Emergency Care Unit, but with a shorter average length of stay. Conclusion: The causes of hospitalization for conditions sensitive to primary care are similar to those in the rest of the country, but there was a significant increase in the rate of hospitalizations due to the Covid-19 pandemic.